A magnesium alloy-resin composite and its preparation method, and electronic product housing
By anodizing the magnesium alloy matrix to form a porous oxide film and injection molding resin, the problem of low bond strength between magnesium alloy and resin is solved, and the effect of high pulling strength and signal transmission is achieved. It is suitable for electronic product shells Lightweight design.
Patent Information
- Application Number
- CN202110150336.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-04
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-02-04
AI Technical Summary
In the prior art, the bonding process of magnesium alloy and resin is complex and the bonding strength is not high, making it difficult to meet the demand for signal transmission of lightweight electronic product shells.
By pretreating the magnesium alloy matrix and anodizing treatment in a high-concentration strong alkaline electrolyte, a porous oxide film is formed, and resin is injected on its surface to form a magnesium alloy-resin composite.
It improves the pulling strength of magnesium alloy and resin, simplifies the process flow, enhances the bonding force between metal and resin, and is suitable for signal transmission of electronic product shells.
Smart Images

Figure 210203094422
Abstract
Description
Technical Field
[0001] The invention relates to the field of materials, and in particular to a magnesium alloy-resin composite and a preparation method thereof, and an electronic product housing. Background Art
[0002] With the advent of 5G technology, the communications industry is developing rapidly. The demand for portability of smart devices such as mobile phones and tablets is increasing day by day, and lightweight mobile devices have become a major development trend. Magnesium and its alloys have high specific strength and specific stiffness, and their density is less than 1 / 4 of steel and only 2 / 3 of aluminum. They are one of the lightest metal structural materials. These advantages make them stand out from many traditional metals and have high potential application prospects in the field of consumer electronics.
[0003] However, the electromagnetic shielding effect of metal causes the signals of electronic products such as mobile phones to be shielded and unable to work normally. In order to solve this problem, a slit is usually opened on the metal body first, and then the slit is filled with resin, and the signal can be sent and received through the resin. When filling the resin, a nano injection molding process is generally used. The specific method is: first, the metal structural part is surface treated to form a surface with micropores, and then the liquid resin is pressed into the micropores by injection molding during the injection molding pressurization process, so that the resin and the metal structural part are integrated into one, and the two have a very high bonding strength. Subsequent pressure processing processes, such as CNC (computer digital control) processing, and the use process have higher requirements on the bonding strength between resin and metal. The surface treatment process of the metal is directly related to the bonding strength between the metal and the resin. However, in the prior art, the process of combining metal and resin is complicated and the bonding strength is not high. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and provide a magnesium alloy-resin composite and a preparation method thereof, as well as an electronic product housing. The method is simple to operate and the magnesium alloy-resin composite has high pulling strength between the magnesium alloy and the resin.
[0005] A first aspect of the present invention is to provide a method for producing a magnesium alloy-resin composite, comprising:
[0006] Providing a magnesium alloy substrate, and pretreating the magnesium alloy substrate;
[0007] Placing the magnesium alloy substrate in an alkaline electrolyte for anodizing treatment to form a porous oxide film on at least a portion of the surface of the magnesium alloy substrate, wherein the alkaline electrolyte comprises a strong base, and the concentration of the strong base in the alkaline electrolyte is 200-600 g / L;
[0008] A resin is injected at a position on the magnesium alloy substrate having the porous oxide film to form the magnesium alloy-resin composite.
[0009] Preferably, the concentration of the strong base in the alkaline electrolyte is 300-500 g / L.
[0010] Preferably, the strong base comprises sodium hydroxide, or potassium hydroxide, or a mixture of sodium hydroxide and potassium hydroxide.
[0011] Preferably, the voltage of the anode during the anodizing process is 10-20V.
[0012] Preferably, the current density of the anode during the anodizing process is 2-10A / dm 2 .
[0013] Preferably, the temperature of the alkaline electrolyte during the anodizing treatment is 10-30° C., and the time of the anodizing treatment is 5-360 s.
[0014] Preferably, the pretreatment comprises at least one of the following steps:
[0015] Degreasing the magnesium alloy substrate in advance;
[0016] Placing the magnesium alloy substrate in an acid etching solution for acid etching;
[0017] Placing the magnesium alloy substrate in an alkaline etching solution for alkaline etching treatment;
[0018] The magnesium alloy substrate is placed in an activation solution for activation treatment.
[0019] Preferably, the acid etching solution comprises a strong acid, the concentration of the strong acid in the acid etching solution is 10-30 g / L, and the acid etching treatment time is 1-2 min.
[0020] Preferably, the alkaline etching solution comprises sodium hydroxide, the concentration of sodium hydroxide in the alkaline etching solution is 20-80 g / L, the alkaline etching temperature is 40-60° C., and the alkaline etching time is 1-5 min.
[0021] Preferably, the activation solution comprises a strong acid, the concentration of the strong acid in the activation solution is 1-5 g / L, and the activation time is 1-5 min.
[0022] Preferably, the thickness of the porous oxide film is 0.05-2 μm, and the diameter of the pores in the porous oxide film is 10-200 nm.
[0023] The second aspect of the present invention is to provide a method for preparing a magnesium alloy-resin composite, wherein the magnesium alloy-resin composite is prepared by the above method.
[0024] A third aspect of the present invention is to provide an electronic product housing, comprising the aforementioned magnesium alloy-resin composite.
[0025] The present invention uses a high-concentration strong alkaline solution to perform anodizing treatment on the surface of the magnesium alloy. The high-concentration alkaline solution has a large conductivity and a high ion exchange rate, so that a nanoporous oxide film layer is generated on the surface of the anodized magnesium alloy, which is stably combined with the resin after injection molding and has excellent pulling strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 FIG. 1 is a SEM morphology of the surface of the magnesium alloy after anodization in one embodiment of the present invention. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] The present invention provides a method for preparing a magnesium alloy-resin composite, comprising:
[0029] Providing a magnesium alloy substrate, and pretreating the magnesium alloy substrate;
[0030] Placing the magnesium alloy substrate in an alkaline electrolyte for anodizing treatment to form a porous oxide film on at least a portion of the surface of the magnesium alloy substrate, wherein the alkaline electrolyte comprises a strong base, and the concentration of the strong base in the alkaline electrolyte is 200-600 g / L;
[0031] A resin is injected at a position on the magnesium alloy substrate having the porous oxide film to form the magnesium alloy-resin composite.
[0032] The present invention uses a high-concentration strong alkaline solution to perform anodizing treatment on the surface of the magnesium alloy. The high-concentration alkaline solution has a large conductivity and a high ion exchange rate, so that a nanoporous oxide film layer is generated on the surface of the magnesium alloy after anodizing, which can be stably combined with the resin after injection molding and has excellent pulling strength.
[0033] The following is a detailed description of each step of the method for preparing a magnesium alloy-resin composite body in conjunction with the specific embodiments of the present application. The method for preparing a magnesium alloy-resin composite body may include:
[0034] S100: providing a magnesium alloy substrate, and pretreating the magnesium alloy substrate;
[0035] According to an embodiment of the present invention, in this step, a magnesium alloy substrate is first provided. According to an embodiment of the present invention, the specific type of the magnesium alloy substrate is not particularly limited, as long as an anodized film composed of aluminum oxide can be formed by anodizing. The specific shape of the magnesium alloy substrate is also not particularly limited, for example, it can be a flat plate, a plate with a curved surface, or a tubular material. It should be noted that in the present invention, the term "magnesium alloy" should be understood broadly, including a magnesium substrate and a magnesium alloy substrate, and the specific model of the magnesium alloy substrate is not particularly limited.
[0036] In order to further improve the efficiency of subsequent treatment, before the subsequent treatment, for example, before the anodizing treatment, the magnesium alloy substrate is pretreated, and the pretreatment includes at least one of the following steps:
[0037] S10: performing a degreasing treatment on the magnesium alloy substrate in advance;
[0038] According to an embodiment of the present invention, in this step, the magnesium alloy substrate may be subjected to a degreasing treatment. Specifically, the magnesium alloy substrate is immersed in a heated degreasing agent for degreasing treatment to remove oil stains on the surface of the magnesium alloy substrate, thereby cleaning the surface of the magnesium alloy and improving the effect of subsequent anodizing treatment. The type of degreasing agent is not limited, as long as it has a certain ability to remove grease-like impurities. For example, in some specific embodiments, the degreasing temperature in the degreasing treatment step is 40-60°C, and the degreasing time is 3-20min.
[0039] S20: placing the magnesium alloy substrate in an acid etching solution for acid etching;
[0040] According to an embodiment of the present invention, after the degreasing treatment, the magnesium alloy substrate may be further subjected to an acid etching treatment. Specifically, the acid etching solution may include a strong acid such as sulfuric acid or hydrochloric acid to corrode the natural oxide layer on the surface of the magnesium alloy substrate, so that the natural oxide layer on the surface of the magnesium alloy substrate peels off, so that the subsequent anodization can be carried out better. For example, in some specific embodiments, the concentration of the strong acid in the acid etching solution is 10-30 g / L, and the acid etching treatment time is 1-2 min.
[0041] S30: placing the magnesium alloy substrate in an alkaline etching solution for alkaline etching treatment;
[0042] According to an embodiment of the present invention, in this step, the magnesium alloy substrate can be alkali-etched by an alkali-etching solution to neutralize the residual acid solution after the acid-etching treatment, and at the same time, the corrosion products generated during the acid-etching treatment are cleaned. For example, in some specific embodiments, the alkali-etching solution includes sodium hydroxide, the concentration of sodium hydroxide in the alkali-etching solution is 20-80 g / L, the alkali-etching temperature is 40-60° C., and the alkali-etching time is 1-5 min.
[0043] S40: placing the magnesium alloy substrate in an activation solution for activation treatment.
[0044] According to an embodiment of the present invention, in this step, the magnesium alloy substrate is immersed in an activation solution to activate the surface of the magnesium alloy substrate, so as to micro-corrode the surface of the magnesium alloy substrate and roughen the surface of the magnesium alloy, so that subsequent anodization can be carried out better. For example, in some specific embodiments, the activation solution may include a strong acid such as sulfuric acid or hydrochloric acid, the concentration of the strong acid in the activation solution is 1-5g / L, and the activation time is 1-5min.
[0045] It should be noted here that, according to some embodiments of the present invention, before anodizing, only degreasing treatment may be performed without acid etching, alkali etching and activation treatment. In other embodiments, degreasing treatment may not be performed, and the magnesium alloy substrate may be directly subjected to acid etching, alkali etching and activation treatment. Similarly, after degreasing treatment, the surface of the magnesium alloy substrate may be secondary cleaned using, but not limited to, deionized water to remove residual degreasing agent. Preferably, degreasing treatment, acid etching, alkali etching and activation treatment are performed in sequence before anodizing, which can better promote the subsequent anodizing.
[0046] S200: placing the magnesium alloy substrate in an alkaline electrolyte for anodizing treatment;
[0047] According to an embodiment of the present invention, in this step, the magnesium alloy substrate is subjected to anodizing treatment. Specifically, in this step, an alkaline electrolyte is used, the alkaline electrolyte includes a strong alkali, and the concentration of the strong alkali in the alkaline electrolyte is 200-600g / L. The high concentration ion state provided by the high concentration strong alkali solution used can generate a high current density on the surface of the magnesium alloy during anodizing. The porous oxide film structure formed on the surface of the magnesium alloy under this high current density can form a stable integrated structure with the resin after injection molding, thereby improving the pulling strength of the magnesium alloy substrate and the resin. According to some embodiments of the present application, the concentration of the strong alkali in the alkaline electrolyte is 300-500g / L, and the strong alkali includes sodium hydroxide, potassium hydroxide, or a mixture of sodium hydroxide and potassium hydroxide.
[0048] Specifically, the thickness of the porous oxide film formed in this step is 0.05-2 μm, and the pore size of the porous oxide film is 10-200 nm. Thus, the porous oxide film can be used to form a complex structure film layer on the surface of the magnesium alloy substrate. The inventors have found through a large number of experiments that this structure is conducive to improving the pulling strength of the magnesium alloy substrate and the resin.
[0049] According to a specific embodiment of the present invention, the magnesium alloy substrate is used as an anode and anodized in an alkaline electrolyte. The anodization treatment can be performed at a voltage of 10-20V or at a current of 2-10A / dm 2 It is carried out at a current density of . It can be understood by those skilled in the art that the anodizing process is a process in which a metal substrate is used as the anode of an electrolytic cell and an oxidation reaction occurs in an alkaline electrolyte. The anodizing process can be controlled by controlling the voltage applied to the anode (i.e., the metal substrate), or, when an inert cathode is selected, the current density of the anode during the anodizing process can also be controlled according to the specific composition and size of the inert cathode (such as a Pt or Au electrode). Therefore, the anodizing process can simultaneously meet the above-mentioned voltage and current density conditions, or it can meet one of the above-mentioned voltage conditions and current density conditions. Thus, a porous oxide film with a thickness of 0.05-2μm can be formed on the surface of the magnesium alloy substrate, and the porous oxide film has a large number of irregularly shaped pores with a pore size of 10-200nm. The pores are nested with each other, which can improve the pull-out strength between the resin and the magnesium alloy substrate formed by the subsequent injection molding process. According to some embodiments of the present application, the anodizing treatment is performed at a voltage of 10-15V, or at 5-9A / dm 2 The current density can further improve the pulling strength between the magnesium alloy matrix and the resin.
[0050] In order to further improve the efficiency of the anodizing treatment, the solution temperature of the alkaline electrolyte can be controlled to be 10-30°C. Under this condition, the anodizing time can be 5-360s, thereby forming a porous oxide film more easily. According to some embodiments of the present application, the solution temperature of the alkaline electrolyte is 15-25°C, and the anodizing time is 10-180s.
[0051] In some embodiments, before the resin is injected, the method may further include the steps of washing and drying the anodized magnesium alloy substrate. Similarly, the washing process in this step may also be performed using deionized water, the purpose of which is to remove the porous oxide film and the residual alkaline electrolyte on the surface of the magnesium alloy substrate. Subsequently, the washed magnesium alloy substrate may be dried, for example, at 60-100° C. More specifically, the magnesium alloy substrate may be placed in an oven and dried.
[0052] S300: Injecting resin at a position on the magnesium alloy substrate where the porous oxide film is formed.
[0053] According to an embodiment of the present invention, in this step, a resin is injected at a position having a porous oxide film on the magnesium alloy substrate to form the magnesium alloy-resin composite. According to an embodiment of the present invention, the specific chemical composition of the resin material used for injection molding in this step is not particularly limited, such as polyphenylene sulfide (PPS), polyamide (PA), polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyaryletherketone resin (PAEK), etc. can be used for injection molding. According to a specific embodiment of the present invention, in this step, nano injection molding technology can be used to combine the resin material with the magnesium alloy substrate. For example, PBT plastic containing 20-45% glass fiber can be used for nano injection molding.
[0054] For example, specifically, an injection mold can be used to form a plastic part having a certain shape by injecting a plastic resin at a specific position of a magnesium alloy substrate, thereby obtaining a magnesium alloy-resin composite.
[0055] The present invention also provides a method for preparing a magnesium alloy-resin composite body, wherein the magnesium alloy-resin composite body is prepared by the above method.
[0056] The present invention also provides an electronic product housing, comprising the aforementioned magnesium alloy-resin composite.
[0057] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.
[0058] Example 1
[0059] Use AZ31B magnesium alloy specimens with a size of 3×12×40mm, put them into a degreasing powder solution at 55℃ for degreasing treatment for 10 minutes; after washing with water, put them into a 20g / L sulfuric acid solution for acid etching for 3 minutes, and then rinse them with water after acid washing; then put them into a 50g / L NaOH solution at 50℃ for alkaline etching for 3 minutes; after washing with water, put them into a 3g / L sulfuric acid solution for activation, and the activation time is 3 minutes. After activation, rinse with water, put them into a 400g / L NaOH solution for anodization, the anodization temperature is 20℃, the anodization time is 60s, the anodization voltage is 13V, and after anodization, rinse them with water and put them into an oven (temperature 80℃) for drying (the scanning electron microscope photo of the porous oxide film formed in the anodization step is shown in the figure). Figure 1 After drying, the magnesium alloy-resin composite A1 was obtained by placing the composite into an injection mold and using PBT resin (containing 40% glass fiber) for injection molding. During the injection molding, the temperature of the injection material was set at 265°C and the mold temperature was set at 150°C.
[0060] Example 2
[0061] The steps of preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the KOH solution with a concentration of 400 g / L is prepared as an alkaline electrolyte.
[0062] Example 3
[0063] The steps of preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the AZ31B magnesium alloy is replaced by the AZ91D magnesium alloy.
[0064] Example 4
[0065] The steps for preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the injection molding material is replaced by PPS containing 25% glass fiber instead of PBT containing 40% glass fiber, and the temperature of the injection molding material is set to 310°C during injection molding.
[0066] Example 5
[0067] The steps for preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the plastic is replaced by PAEK containing 30% glass fiber instead of PBT containing 40% glass fiber, and the temperature of the injection molding material is set to 390°C and the mold temperature is set to 210°C during injection molding.
[0068] Example 6
[0069] The steps for preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the composite is placed in a 300 g / L NaOH solution for anodization.
[0070] Example 7
[0071] The steps for preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the composite is placed in a 500 g / L NaOH solution for anodization.
[0072] Example 8
[0073] The steps for preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the composite is placed in a 200 g / L NaOH solution for anodization.
[0074] Example 9
[0075] The steps for preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the composite is placed in a 600 g / L NaOH solution for anodization.
[0076] Example 10
[0077] The steps of preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the anodizing voltage is 10V.
[0078] Embodiment 11
[0079] The steps of preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the anodizing voltage is 20V.
[0080] Example 12
[0081] The steps of preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the anodizing voltage is 5V.
[0082] Example 13
[0083] The steps of preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the anodizing voltage is 30V.
[0084] Embodiment 14
[0085] The steps for preparing the magnesium alloy-resin composite in this embodiment are the same as those in Embodiment 1, except that the anodizing time is 300 s.
[0086] Comparative Example 1
[0087] The steps for preparing the magnesium alloy-resin composite in this comparative example are the same as those in Example 1, except that the composite is placed in a 50 g / L NaOH solution for anodization.
[0088] Comparative Example 2
[0089] The steps for preparing the magnesium alloy-resin composite in this comparative example are the same as those in Example 1, except that the composite is placed in a 800 g / L NaOH solution for anodization.
[0090] Performance Test:
[0091] Pull-out strength: The pull-out test was conducted on a universal material testing machine (model: INSTRON 3369), with a pulling speed of 5 mm / min and a unit of MPa (acting on a unit area (mm 2 ) (N)).
[0092] Table 1
[0093] sample Pull-out strength / MPa Example 1 42.52 Example 2 41.23 Example 3 43.36 Example 4 49.55 Example 5 40.71 Example 6 40.23 Example 7 41.62 Example 8 38.23 Example 9 40.86 Example 10 38.65 Embodiment 11 37.55 Example 12 34.32 Example 13 33.53 Embodiment 14 40.92 Comparative Example 1 25.53 Comparative Example 2 26.78
[0094] It can be seen from the results in Table 1 that the pull-out strength between the magnesium alloy and the resin in the magnesium alloy-resin composite prepared by the method provided by the present invention is high. By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that when the concentration of the alkaline electrolyte is too low or too high, the pull-out strength between the magnesium alloy and the resin in the prepared magnesium alloy-resin composite is less than 30 MPa.
[0095] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0096] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0097] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a magnesium alloy-resin composite, characterized in that: include: Providing a magnesium alloy substrate, and pretreating the magnesium alloy substrate; Placing the magnesium alloy substrate in an alkaline electrolyte for anodizing treatment to form a porous oxide film on at least a portion of the surface of the magnesium alloy substrate, wherein the alkaline electrolyte comprises a strong base, and the concentration of the strong base in the alkaline electrolyte is 200-600 g / L; Injecting resin at a position on the magnesium alloy substrate having the porous oxide film to form the magnesium alloy-resin composite; The voltage of the anode during the anodizing process is 10-20V; The current density of the anode during the anodizing process is 2-10A / dm 2 ; The thickness of the porous oxide film is 0.05-2μm, and the pore size of the porous oxide film is 10-200nm.
2. The method according to claim 1, characterized in that: The concentration of the strong alkali in the alkaline electrolyte is 300-500 g / L.
3. The method according to claim 1 or 2, characterized in that: The strong base includes sodium hydroxide, potassium hydroxide, or a mixture of sodium hydroxide and potassium hydroxide.
4. The method according to claim 1, characterized in that When the anodizing treatment is performed, the temperature of the alkaline electrolyte is 10-30° C., and the time of the anodizing treatment is 5-360 seconds.
5. The method according to claim 1, characterized in that The pre-processing comprises at least one of the following steps: Degreasing the magnesium alloy substrate in advance; Placing the magnesium alloy substrate in an acid etching solution for acid etching; Placing the magnesium alloy substrate in an alkaline etching solution for alkaline etching treatment; The magnesium alloy substrate is placed in an activation solution for activation treatment.
6. The method according to claim 5, characterized in that The acid etching solution includes a strong acid, the concentration of the strong acid in the acid etching solution is 10-30 g / L, and the acid etching treatment time is 1-2 min.
7. The method according to claim 5, characterized in that The alkaline etching solution comprises sodium hydroxide, the concentration of sodium hydroxide in the alkaline etching solution is 20-80 g / L, the alkaline etching temperature is 40-60° C., and the alkaline etching time is 1-5 min.
8. The method according to claim 5, characterized in that The activation solution includes a strong acid, the concentration of the strong acid in the activation solution is 1-5 g / L, and the activation time is 1-5 min.
9. A magnesium alloy-resin composite, characterized in that: The magnesium alloy-resin composite is prepared by the method according to any one of claims 1 to 8.
10. An electronic product housing, characterized in that: It comprises the magnesium alloy-resin composite body as claimed in claim 9.
Citation Information
Patent Citations
Electrolyte for anodic oxidation treatment of magnesium alloy and treatment method thereof
CN102653877A
Metal-resin compound and preparation method thereof
CN105196652A